2019
DOI: 10.18517/ijaseit.9.4.8844
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Stemmer Porter Effect and Nazief-Adriani on the Performance of Winnowing Algorithms for Measuring Plagiarism

Abstract: Current technological developments change physical paper patterns into digital, and this has a very high impact. Positive impact because paper waste is reduced, on the other hand, the rampant copying of digital data raises the amount of plagiarism that is increasing. At present, there are many efforts made by experts to overcome the problem of plagiarism, one of which is by utilizing the winnowing algorithm as a tool to detect plagiarism data. In its development, many optimizing winnowing algorithms used stemm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…If the algorithm is failed in doing all steps above, then the first word is assumed to be the base word. So the process is complete [10].…”
Section: ) Recordingmentioning
confidence: 99%
“…If the algorithm is failed in doing all steps above, then the first word is assumed to be the base word. So the process is complete [10].…”
Section: ) Recordingmentioning
confidence: 99%
“…Their work consisted of 5 stages from pre-processing to similarity detection. Rahmatulloh et al [14] demonstrated a difference between the Nazief-Adriani and stemmer porter in measuring plagiarism. This study indicates Nazief-Adriani performs superior to the stemmer porter.…”
Section: Introductionmentioning
confidence: 99%
“…Research by A. Rahmatulloh et al [5] discuss the comparative performance of Porter and Nazief & Adriani stemming on the Winnowing algorithm for plagiarism detection. The results of the study concluded that testing the Winnowing algorithm without stemming had the results of 70.7% plagiarism similarity with processing speed of 0.711 s, Winnowing algorithm testing with stemming Porter had the results of plagiarism similarity of 65.7% with processing speed of 0.221 s, testing of the Winnowing algorithm with Nazief & Adriani stemming had results plagiarism similarity 70.5% with processing speed 0.476 s. Stemming Porters reduce the level of plagiarism similarity results very significantly but speed up processing while Nazief & Adriani stemming results are close to the same as without using stemming and also speed up processing.…”
Section: Introductionmentioning
confidence: 99%